THE GROWTH, DEVELOPMENT AND FEATURES OF BOTANICAL HERBAGE FORMATION OF BIRDS’ FOOT TREFOIL WITH TIMOTHY DEPENDING ON FERTILIZER - Оліфірович, В. О. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The research aim was to study the characteristics of the height formation, density and botanical composition of legume-cereal grass depending on the use of phosphorus, molybdenum fertilizers and Rhizobofit. Bookmarks experiments, surveys and monitoring were carried out in accordance withconventional techniques for crop and forage production. Shoot density measured on four pitches of 0.25 m2 on two non-adjacent repetitions before each mowing and plant height was measured before collectingeach mowing. Botanical composition was determined by selecting from two non-contiguous repetitions of 1 kg herb. Herbs were divided into the following groups: legumes, cereals, grasses, while defining the types of legumes and grasses. Collated grass weighed and calculated the portion of each in % by weight of the entire sample. It was established that on sloping lands south- western forest-steppe maximum height of plantslegume-cereal grass was on variant with treatment Rhizobofit seeds and making 60 kg/ha of active ingredient of phosphate fertilizers: the height of birds foot trefoil in the first mowing - 44.1 sm, second - 32.9 sm; timothy grass height in the first mowing - 48.8 sm, second - 32.1 sm average for 2013-2015 years the maximum number of bean sprouts component is fixed on a variant with a combination of the phosphatefertilizers use and Rhizobofit - 617 pcs/m2 in the first and 510 pcs/m2 in the second cut. In the dynamics of the three-year maximum density of legume-grass sward was reached in the first mowing of 2014, in thesecond year of use. The maximum proportion of legume component in all variants of the experiment in the first mowing was observed in 2014. Thus, in the control (without fertilizer) share a birds’ foot trefoil was53.5%. This mowing the most powerful factor in increasing the percentage of legumes turned phosphorus fertilization, whereby the proportion of a birds’ foot trefoil rose to 56.4%. Indicators plant height and density shoots indicate that the maximum development of herbagebirds foot trefoil timothy-grass was reached in the second year of use. Phosphate fertilizers contributed to the preservation and Rhizobofit bean component of grass mixtures, whose share was at the end of studies64.5-68.5%.